MANAKAH INDIKATOR TERPENTING STABILITAS SISTEM KEUANGAN?PERSPEKTIF MAKROPRUDENSIAL - Aam Slamet Rusydiana; Lina Nugraha Rani; Fatin Fadhilah Hasib (Jurnal Ekonomi dan Pembangunan, 2025)
The financial system stability of Indonesia is generally measured in two ways, namely microprudential and macroprudential. Among macroprudential indicators they are economic growth, balance of payments, inflation rate, interest and exchange rates, crisis contagion effect, and many others. Different from the previous researches, this research utilises financial and banking practitioners’ perspective to determine the leading indicator of financial system stability using Analytic Network Process (ANP) method. The results show that, the three most important indicators of Indonesia’s financial stability at macro levels include the Debt-related aspect (0.225), Macroeconomic Indicator (0.222) and the Balance of Payment aspect (0.217). The other important indicators of financial system stability is related to Contagion Effect (0.178) and the Labor-related aspects (0.159). The Macroprudential Policy issued by Bank Indonesia, play an important role in maintaining Financial System Stability (SSK) in Indonesia.